(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
We are presenting a case report of heterotopic pregnancy, which is diagnosed during ultrasound examination of a gravid woman, 23 year old, referred from outpatient department. Heterotopic pregnancy is a rare obstetrics phenomenon and carries a significant natural morbidity and mortality due to risk of rupture of the ectopic pregnancy. Clinicians and sonographers may fall into a false sense of security when an intrauterine gestational sac is identified. This results in inadequate inspection of the adnexae and remaining structures during ultrasonography despite a strong initial clinical suspicion of ectopic pregnancy. Hence, a thorough ultrasonographic examination is needed in managing these patients, especially when there is a high suspicion of ectopic pregnancy or in the presence of pelvic free fluid even when an intrauterine pregnancy is identified. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22888 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 64-66